2016
DOI: 10.1158/0008-5472.can-16-0618
|View full text |Cite
|
Sign up to set email alerts
|

Ccl22 Diverts T Regulatory Cells and Controls the Growth of Melanoma

Abstract: T regulatory cells (Treg) avert autoimmunity but their increased levels in melanoma confer a poor prognosis. To explore the basis for Treg accumulation in melanoma, we evaluated chemokine expression in patients. A 5-fold increase was documented in the Treg chemoattractants CCL22 and CCL1 in melanoma-affected skin versus unaffected skin, as accompanied by infiltrating FoxP3+ T cells. In parallel, there was a ~2-fold enhancement in expression of CCR4 in circulating Treg but not T effector cells. We hypothesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…Consistently, the expression level of CCL22 was higher in HepG2.2.15 cells (HBV + ) than HepG2 (HBV − ) and WRL68 (normal) cells. Given that CCL22 acted as an essential attractive signal of Tregs recruitment in various cancers, and that Foxp3 was the highly specific marker of Tregs, higher CCL22 and Foxp3 levels in HBV + tumor implied higher intratumoral Tregs infiltration than HBV ‐ tumors. In contrast, miR‐23a expression was found to be inversely correlated with both CCL22 and Foxp3, particularly in HBV + tumors (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, the expression level of CCL22 was higher in HepG2.2.15 cells (HBV + ) than HepG2 (HBV − ) and WRL68 (normal) cells. Given that CCL22 acted as an essential attractive signal of Tregs recruitment in various cancers, and that Foxp3 was the highly specific marker of Tregs, higher CCL22 and Foxp3 levels in HBV + tumor implied higher intratumoral Tregs infiltration than HBV ‐ tumors. In contrast, miR‐23a expression was found to be inversely correlated with both CCL22 and Foxp3, particularly in HBV + tumors (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Among these chemokines, CCL2, CCL3, CCL4, CCL5, CXCL9, and CXCL10 were preferentially expressed in lesions characterized by immune cell infiltration, including T cells. 18 However other chemokines are expressed in the tumor microenvironment of melanoma, such as CXCL8/IL-8, CXCL12/SDF1, 18 and CCL22, 19 which have been associated with promoting tumor growth through induction of angiogenesis, metastasis and recruitment of immune regulatory cell subsets, such as myeloid derived suppressor cells (MDSC) and regulatory T cells (Tregs). 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
“…They concluded that IQM could be used to control dermal metastatic melanoma, but that intralesional IL-2 is indispensable for controlling subcutaneous melanoma, suggesting that the abrogation of regulatory T cell (Treg) function is necessary for induction of an antitumor immune response by IQM (9). CCL22 attracts chemokine (C-C motif) ligand 4 (CCR4) + T cells, including Tregs, in the lesional skin of melanoma (12). As Klarquist et al reported, CCL22-related Tregs drive B16F10 melanoma growth in vivo, and the diversion of Tregs to normal skin by CCL22 vaccination could limit tumor-infiltrating Tregs, subsequently suppressing melanoma growth (12).…”
mentioning
confidence: 99%
“…CCL22 attracts chemokine (C-C motif) ligand 4 (CCR4) + T cells, including Tregs, in the lesional skin of melanoma (12). As Klarquist et al reported, CCL22-related Tregs drive B16F10 melanoma growth in vivo, and the diversion of Tregs to normal skin by CCL22 vaccination could limit tumor-infiltrating Tregs, subsequently suppressing melanoma growth (12). In addition, as we previously reported, immunomodulatory drugs such as interferons (IFNs) could modulate CCL22 production from TAMs to decrease Treg recruitment to the tumor (13).…”
mentioning
confidence: 99%